The method of determining the efficiency of the complex treatment of comorbid states tuberculosis-herpesvirus infections - Voliansky , Andrii; Smilyanskaya, Maiia; Didorenko, Tetiana; Sukhanova, Lydia; Zosymov, Anatoly; Herasimova, Tetiana (Annals of Mechnikov’s Institute, 2023)
The proposed method includes establishing the integral coefficient of cytokine balance by determining the value of the interleukin indices as the ratio of the parameters of the pro- and anti-inflammatory opposite groups in the blood serum to the reference values, calculating the arithmetic averages for each group, establishing the integral cytokine index (integral cytokine index, ICI).